Destruction of Communicative Pragmatics in Contemporary Absurdist Dramaturgic Texts - Валерія Корольова; Ірина Попова (Психолінгвістика)
The aim of the article is characteristics of mechanisms of pragmatics distraction in communication of active participants of modern Ukrainian plays with features of the theatre of the absurdity. Structural and contextual mechanisms of dialogic speech depragmatization are singled out on factual material. In a dramatic dialogue absurdity is explained as a purposeful instruction to convey the thought about illogicalness and chaotic nature of reality, the aimlessness of a human being. The main methods of the study are descriptive, context-interpreting and presuppositional.